U-Pb dating of speleothems from Spannagel Cave, Austrian Alps: a high resolution comparison with U-series ages - Cliff, Robert A.; Spötl, Christoph; Mangini, Augusto (Quaternary geochronology, 2010)
U-Pb dating is increasingly used to date speleothems that are too old for precise U-Th disequilibrium dating; however there is little data that can independently validate its application to such material. This study presents U-Pb ages for speleothems from the Spannagel Cave in the Austrian Alps including a detailed comparison with U-Th ages from an unusually U-rich sample that yields precise ages by both methods. Sample SPA4 is a flowstone with three growth phases separated by distinct hiatuses. For the youngest growth phase the U-Pb and U-Th ages are 267±1ka and 267±5ka respectively; the middle growth phase is 291±1 versus 295±11ka while for the oldest growth phase a single sub-sample, assuming the same initial Pb composition as for the younger phases, yields an age of 340±2ka compared to 353±9ka by U-Th. Correlation of these ages with the marine isotope stages confirms that these speleothems grew during glacial stages as suggested by previous work on the same sample. Sample SPA 15 has U-Th isotopic compositions indistinguishable from secular equilibrium; the U-Pb data on the main growth phase of this sample give an age of 551±10ka, whereas a single analysis from the oldest phase suggests it may be on the order of 40ka older. This detailed comparison of U-Pb and U-Th ages provides important support for the potential validity of the U-Pb method in older samples beyond the range of U-Th.
Available online 22 December 2009
Gesehen am 05.05.2023